Fundamental of Entrepreneurship (ENT300) Business Plan Merak Relaxing Centre (MRC) / Muhammad Asyraf Nazman...[et al.] - Nazman, Muhammad Asyraf; Hassan, Nur Hafizah; Mohd Mokhtar, Noor Syahira; Mohd Ramzi, Nur Fatin Syafiqah; Shabudin, Nur Syahidah; Ismail, Nur Syamimi; Ayob, Nurul Nabilah (2019)
Merak Relaxing Centre will establish on 3 March 2020 at Tasik Merak, UiTM Kedah. There are seven partners involve in this business. Our objective is to be the first relaxing centre at UiTM Kedah. The average price students able to pay is RM1- RM20 per service.